Transcriptional mapping of the vaccinia virus DNA polymerase gene. - Jones, E V (1985)
Transcriptional analysis of the vaccinia virus DNA polymerase gene revealed the presence of overlapping RNAs. Cloned DNA fragments, previously shown to lie within the DNA polymerase gene (E. V. Jones and B. Moss, J. Virol. 49:72-77, 1984) hybridized to early RNA species of ca. 3,400 and 3,700 nucleotides. Nuclease S1 analysis was used to determine the direction of transcription and more precisely map the mRNAs. A single 5' end and two major and one minor 3' ends were detected.